Bartonella osteomyelitis versus vertebral sarcoidosis: A tale of two cases. Issue 2 (April 2021) - Soni, Neetu; Gupta, Sarika; Pillenahalli Maheshwarappa, Ravishankar; Priya, Sarv; Bathla, Girish
Background: Osteomyelitis is an uncommon manifestation of Bartonella henselae. Similarly, bony involvement may occur with sarcoidosis. Even though these are pathologically distinct entities, they can have overlapping imaging manifestations and therefore mimic one another. This is further complicated by the fact that both entities show non-caseating granulomatous inflammation on histopathology. We present two cases with similar imaging findings, with one case eventually diagnosed as Bartonella osteomyelitis, while the other proved to be vertebral sarcoidosis. Both patients exhibited vertebral involvement in common, and improved clinically and radiographically following antibiotics and steroids treatment, respectively. Given the overlapping pathological and imaging manifestations, and the non-specific clinical presentation, these entities may be considered in the differential consideration of each other. The presence of associated findings in such cases may be helpful.